Oxygen, nitrogen and sulphide fluxes in the Black Sea - KONOVALOV, S.K.; IVANOV, L.I.; SAMODUROV, A.S. (Mediterranean Marine Science, 2000)
The fluxes and production/consumption rates of oxygen, nitrate, ammonium and sulphide are estimated in the paper utilising results of the 1.5-dimensional stationary model of vertical exchange in the Black Sea (Samodurov & Ivanov, 1998). The profiles of the vertical flux and rate of production/consumption of these substances have revealed a number of intriguing features in the biogeochemical nature of the Black Sea. An approximate redox balance of the counter-fluxes of nitrate and ammonium into the sub-oxic zone has been revealed confirming that intensive denitrification may be the primary loss of nitrogen in the Black Sea. A low ratio of the nitrate stock to the flux of nitrate from the oxycline confirms the possibility of prominent changes in the distribution of nitrate on the time scale of a year. The ratio of the nitrate to oxygen vertical flux has revealed a lack of nitrate in the oxycline above the nitrate maximum. The lateral (related to the "Bosporus plume") flux of oxygen in the layer of the main pycnocline appears to be very important for the existing biogeochemical structure of the Black sea water column being the reason of sulphide consumption inside the anoxic zone and changes in the ammonium-sulphide stoichiometry of the anoxic zone, the primary reason of the existence of the sub-oxic layer and the basic reason of relative stability of the sulphide onset.